Packet Throughput In Hybrid Ds/Sfh Cdma Slotted Aloha Systems For Wireless Communications - Dabbang, Prach; Varakusiripunth, Ruttikorn (Frontiers in Engineering Innovation Research, 2002)
The hybrid direct -sequence/slow frequency hopping code division multiple-access (OS/ SFH COMA) technique is CDMA processing gain and FEC capability produces an increase in maximum peak of channel throughput and offered load. The throughput of this channel is compared to the multichannel narrow-band slotted ALOHA proposed for wireless packet transmission channel. We consider that the channel is hybrid OS/SFH COMA slotted ALOHA ( HCOMA) channel. The probability of packet success and channel throughput are derived. The numerical analysis will be performed with several level of processing gain and forward error correction (FEC) capability. The numerical results show that an increase in H-CDMA processing in maximum peak of channel throughput and offered load. The throughput of this channel is compared to the multichannel narrow-band slotted ALOHA (M- ALOHA) channel that occupies approximately the same bandwidth. At offered load level below and slightly above the point that achieve maximum peak throughput, the H-CDMA produces throughput better than the M-ALOHA.